Exercise and Inflammatory Response: Mechanism of Interleukin-6 Expression Changes - Delvy Atriani; Irfannuddin Irfannuddin; Budi Santoso (GLOBAL HEALTH SCIENCE GROUP, 2026)
Exercise has a broad impact on health through various physiological mechanisms, one of which is through the regulation of interleukin-6 (IL-6). IL-6 is a pleiotropic cytokine that plays a role in immune responses, inflammation, and energy metabolism regulation, and is produced not only by immune cells but also by skeletal muscle as myokine during physical activity. This article aims to examine the physiological adaptations of exercise to IL-6 production and function and its relationship to energy metabolism, mitochondrial function, and inflammatory response. The research method employed was a literature review utilizing a descriptive approach. In acute exercise, muscle contraction triggers a rapid and temporary increase in IL-6 through mechanisms involving changes in calcium homeostasis, activation of AMP-activated protein kinase (AMPK) due to decreased energy reserves, oxidative stress, and epigenetic regulation. This study was conducted using a descriptive literature review approach. Relevant primary research articles and review papers were systematically identified through electronic databases, the selected literature was analyzed and synthesized to explore the mechanisms underlying exercise-induced changes in Interleukin-6 (IL-6) expression and signaling, with particular emphasis on acute and chronic exercise adaptations, energy metabolism, mitochondrial function, and inflammatory responses. The increase in IL-6 during this phase plays a role in maintaining energy homeostasis by increasing glucose transport, fatty acid oxidation, and modulating the immune response. Conversely, regular exercise induces long-term adaptations in the form of increased mitochondrial number and function, increased antioxidant capacity, and increased muscle sensitivity to IL-6 through the classical signaling pathway. These adaptations enhance IL-6 signaling efficiency, enabling metabolic and anti-inflammatory responses to be achieved with lower IL-6 production. Thus, regular exercise plays a crucial role in reducing systemic inflammation, improving energy metabolism, and supporting health and the prevention of chronic diseases.